Enhanced Electrochemical Properties of Na0.67MnO2 Cathode for Na-Ion Batteries Prepared with Novel Tetrabutylammonium Alginate Binder - Gints Kucinskis; Beate Kruze; Prasad Korde; Anatolijs Sarakovskis; Arturs Viksna; Julija Hodakovska; Gunars Bajars (Batteries, 2022)
Both the binder and solid–electrolyte interface play an important role in improving the cycling stability of electrodes for Na-ion batteries. In this study, a novel tetrabutylammonium (TBA) alginate binder is used to prepare a Na0.67MnO2 electrode for sodium-ion batteries with improved electrochemical performance. The ageing of the electrodes is characterized. TBA alginate-based electrodes are compared to polyvinylidene fluoride- (PVDF) and Na alginate-based electrodes and show favorable electrochemical performance, with gravimetric capacity values of up to 164 mAh/g, which is 6% higher than measured for the electrode prepared with PVDF binder. TBA alginate-based electrodes also display good rate capability and improved cyclability. The solid–electrolyte interface of TBA alginate-based electrodes is similar to that of PVDF-based electrodes. As the only salt of alginic acid soluble in non-aqueous solvents, TBA alginate emerges as a good alternative to PVDF binder in battery applications where the water-based processing of electrode slurries is not feasible, such as the demonstrated case with Na0.67MnO2.